'The Stuff of Slow Constitution': Reading Down Syndrome for Race, Disability, and the Timing that Makes Them So. (September 2016) - Chen, Mel Y.
Abstract : In this paper I would like to bring into historical perspective the interrelation of several notions such as race and disability, which at the present moment seem to risk, especially in the fixing language of diversity, being institutionalised as orthogonal in nature to one another rather than co-constitutive. I bring these notions into historical clarity primarily through the early history of what is today known as Down Syndrome or Trisomy 21, but in 1866 was given the name 'mongoloid idiocy' by English physician John Langdon Down. In order to examine the complexity of these notions, I explore the idea of 'slow' populations in development, the idea of a material(ist) constitution of a living being, the 'fit' or aptness of environmental biochemistries broadly construed, and, finally, the germinal interarticulation of race and disability – an ensemble that continues to commutatively enflesh each of these notions in their turn.